Low-temperature sintering and electrical properties of strontium- and magnesium-doped lanthanum gallate with V2O5 additive - Ha, Sang Bu; Cho, Yoon Ho; Ji, Ho-Il; Lee, Jong-Ho; Kang, Yun Chan; Lee, Jong-Heun (ELSEVIER, 2011)
The effects of a V2O5 additive on the low-temperature sintering and ionic conductivity of strontium- and magnesium-doped lanthanum gallate (LSGM: La0.8Sr0.2Ga0.8Mg0.2O2.8) are studied. The LSGM powders prepared by the glycine nitrate method are mixed with 0.5-2 at.% of VO5/2 and then sintered at 1100-1400 degrees C in air for 4 h. The apparent density and phase purity of the LSGM specimens are increased with increasing sintering temperature and VO5/2 concentration due to the enhanced sintering and mass transfer via the intergranular liquid phase. The 1 at.% VO5/2-doped LSGM specimen sintered at 1300 degrees C exhibits a high oxide ion conductivity of similar to 0.027 S cm(-1) at 700 degrees C over a wide range of oxygen partial pressure (P-O2 = 10(-27) - 1 atm), thereby demonstrating its potential as a useful electrolyte for anode-supported solid oxide fuel cells (SOFCs) without the requirement for any buffer layer between the electrolyte and anode. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: GRAIN-BOUNDARY CONDUCTION; OXIDE-ION CONDUCTIVITY; FUEL-CELLS; MICROSTRUCTURAL CHARACTERIZATION; LAGAO3; ELECTROLYTE; LSGM; ANODE; PERFORMANCE; CERAMICS